Organization, Phylogenetic Marker Exploitation, and Gene Evolution in the Plastome of Thalictrum (Ranunculaceae) - Xiang, Kun-Li; Mao, Wei; Peng, Huan-Wen; Erst, Andrey S.; Yang, Ying-Xue; He, Wen-Chuang; Wu, Zhi-Qiang (Frontiers in Plant Science, 2022)
Thalictrum is a phylogenetically and economically important genus in the family Ranunculaceae, but is also regarded as one of the most challengingly difficult in plants for resolving the taxonomical and phylogenetical relationships of constituent taxa within this genus. Here we sequenced the complete plastid genomes of two Thalictrum species using Illumina sequencing technology via de novo assembly. The two Thalictrum plastomes exhibited circular and typical quadripartite structure that was rather conserved in overall structure and the synteny of gene order. By updating the previously reported plastome annotation of other nine Thalictrum species, we found that the expansion or contraction of the inverted repeat region affect the boundary of the single-copy regions in Thalictrum plastome. We identified eight highly variable noncoding regions—infA-rps8, ccsA-ndhD, trnSUGA-psbZ, trnHGUG-psbA, rpl16-rps3, ndhG-ndhI, ndhD-psaC and ndhJ-ndhK—that can be further used for molecular identification, phylogenetic, and phylogeographic in different species. Selective pressure and codon usage bias of all the plastid coding genes were also analyzed for the 11 species. Phylogenetic relationships showed Thalictrum is monophyly and divided into two major clades based on 11 Thalictrum plastomes. The availability of these plastomes offers valuable genetic information for accurate identification of species and taxonomy, phylogenetic resolution and evolutionary studies of Thalictrum, and should assist with exploration and utilization of Thalictrum plants.